Direct visualization of KirBac3.1 potassium channel gating by atomic force microscopy. - Jarosławski, S; Zadek, B; Ashcroft, F; Vénien-Bryan, C; Scheuring, S (2007)
KirBac3.1 belongs to a family of transmembrane potassium (K(+)) channels that permit the selective flow of K-ions across biological membranes and thereby regulate cell excitability. They are crucial for a wide range of biological processes and mutations in their genes cause multiple human diseases. Opening and closing (gating) of Kir channels may occur spontaneously but is modulated by numerous intracellular ligands that bind to the channel itself. These include lipids (such as PIP(2)), G-proteins, nucleotides (such as ATP) and ions (e.g. H(+), Mg(2+), Ca(2+)). We have used high-resolution atomic force microscopy (AFM) to examine KirBac3.1 in two different configurations. AFM imaging of the cytoplasmic surface of KirBac3.1 embedded in a lipid bilayer has allowed visualization of the tetrameric assembly of the ligand-binding domain. In the absence of Mg(2+), the four subunits appeared as four protrusions surrounding a central depression corresponding to the cytoplasmic pore. They did not display 4-fold symmetry, but formed a dimer-of-dimers with 2-fold symmetry. Upon addition of Mg(2+), a marked rearrangement of the intracellular ligand-binding domains was observed: the four protrusions condensed into a single protrusion per tetramer, and there was an accompanying increase in protrusion height. The central cavity within the four intracellular domains also disappeared on addition of Mg(2+), indicating constriction of the cytoplasmic pore. These structural changes are likely transduced to the transmembrane helices, which gate the K(+) channel. This is the first time AFM has been used as an interactive tool to study K(+) channels. It has enabled us to directly measure the conformational changes in the protein surface produced by ligand binding.